Efficacy and safety of certolizumab pegol monotherapy every 4 weeks in patients with rheumatoid arthritis failing previous disease-modifying antirheumatic therapy: the FAST4WARD study. Issue 6 (17th November 2008) - Fleischmann, R; Vencovsky, J; van Vollenhoven, R F; Borenstein, D; Box, J; Coteur, G; Goel, N; Brezinschek, H-P; Innes, A; Strand, V
Abstract : Background: Tumour necrosis factor α (TNFα) is a proinflammatory cytokine involved in the pathogenesis of rheumatoid arthritis (RA). Treatment with TNFα inhibitors reduces disease activity and improves outcomes for patients with RA. This study evaluated the efficacy and safety of certolizumab pegol 400 mg, a novel, poly-(ethylene glycol) (PEG)ylated, Fc-free TNFα inhibitor, as monotherapy in patients with active RA. Methods: In this 24-week, multicentre, randomised, double-blind, placebo-controlled study, 220 patients previously failing ⩾1 disease-modifying antirheumatic drug (DMARD) were randomised 1:1 to receive subcutaneous certolizumab pegol 400 mg (n = 111) or placebo (n = 109) every 4 weeks. The primary endpoint was 20% improvement according to the American College of Rheumatology criteria (ACR20) at week 24. Secondary endpoints included ACR50/70 response, ACR component scores, 28-joint Disease Activity Score Erythrocyte Sedimentation Rate 3 (DAS28(ESR)3), patient-reported outcomes (including physical function, health-related quality of life (HRQoL), pain and fatigue) and safety. Results: At week 24, the ACR20 response rates were 45.5% for certolizumab pegol 400 mg every 4 weeks vs 9.3% for placebo (p<0.001). Differences for certolizumab pegol vs placebo in the ACR20 response were statistically significant as early as week 1 through to week 24 (p<0.001). Significant improvements in ACR50, ACR components, DAS28(ESR)3 and all patient-reported outcomes were also observed early with certolizumab pegol and were sustained throughout the study. Most adverse events were mild or moderate and no deaths or cases of tuberculosis were reported. Conclusions: Treatment with certolizumab pegol 400 mg monotherapy every 4 weeks effectively reduced the signs and symptoms of active RA in patients previously failing ⩾1 DMARD compared with placebo, and demonstrated an acceptable safety profile. Trial registration number: NCT00548834.